2017
DOI: 10.3390/urbansci1020017
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Modeling Approach to Health-Related Urban Well-Being

Abstract: Abstract:In cities, social well-being faces obstacles posed by globalization, demographic and climate change, new forms of social organization, and the fragmentation of lifestyles. These changes affect the vulnerability of city societies and impact their health-related urban well-being (UrbWellth). The conceptual model introduced in this paper systematizes the relevant variables while considering previous research, and establishes the target value UrbWellth. The model differs from existing approaches mainly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 133 publications
1
37
0
Order By: Relevance
“…Therefore, we argue that the health effect of noise is not independent of the rating on subjective annoyance [83,97]. This raises the questions if habituation [21] (due to a long period of residence) or declining hearing capacity with increasing age could have a positive effect on noise annoyance and thus also on other health outcomes (such as hypertension). However, results of Riedel et al suggest that self-reported hearing disability enhanced noise annoyance [34].…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we argue that the health effect of noise is not independent of the rating on subjective annoyance [83,97]. This raises the questions if habituation [21] (due to a long period of residence) or declining hearing capacity with increasing age could have a positive effect on noise annoyance and thus also on other health outcomes (such as hypertension). However, results of Riedel et al suggest that self-reported hearing disability enhanced noise annoyance [34].…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 99%
“…Additionally, several questions were derived from the UrbWellth model [21]. The whole questionnaire was repeatedly pre-tested.…”
Section: Study Areas and Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this city, several research projects investigated the urban system with all its components leading to a conceptual model with a focus on urban health and wellbeing [4]. However, to quantitatively describe reactions of the urban system to external and internal changes in meteorological parameters and land cover, the signals from both origins need to be distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…All of these environmental stressors have elevated levels compared to their rural surroundings [4][5][6]. However, there are several factors that affect the impact of such stressors on health discussed by von Szombathely et al [7] in their conceptual model for health-related urban well-being (UrbWellth). For instance, environmental stressors can only lead to a higher mortality or morbidity if urban dwellers are exposed to them (e.g., being outside).…”
Section: Introductionmentioning
confidence: 99%